Non-motor symptoms in a Flanders-Belgian population of 215 Parkinson’s disease patients as assessed by the Non-Motor Symptoms Questionnaire - Crosiers, David (e-Century Publishing Corporation, 2012)
Background: Non-motor symptoms (NMS) in Parkinson’s disease (PD) are frequent, increase the patients’ disability and have an important negative impact on their quality of life. Methods: We used a Dutch translation of the Non-Motor Symptoms Questionnaire (NMSQuest) to identify NMS in a population of 215 Belgian PD patients. Results: A median number of 8 NMS was reported per patient. Urinary urgency (59.2 %), nocturia (56.9 %), insomnia (45.8 %), attention problems (45.5 %) and orthostatism (41.2 %) were the most frequently denoted NMS. A higher number of NMS was present with more severe Hoehn and Yahr stages. Longer disease duration was associated with more NMS. Furthermore, clinical markers of disease progression were also associated with a higher number of NMS. However, early-onset patients (< 50 years) reported less NMS than late-onset patients after correction for disease duration. Interestingly, in early-onset patients we observed more unexplained pain and more hyperhydrosis. Conclusion: We confirm the high prevalence of NMS in PD patients. A long disease duration and more severe disease are associated with a higher number of NMS. Importantly, even if late-onset patients generally report more NMS, unexplained pain and hyperhydrosis are more frequent in early-onset patients.